Pengaruh Keamanan Two Factor Authentication Terhadap Pencurian Data (Cyber Crime) Pada Media Sosial - Aprilia, Tantri; Pitoyo, Bayu Seno; Fauzi, Achmad; Ramadhanti, Reifa Galih; Nurazizah, Rizty Dwi; Wanti, Eny Trisno; Nugroho, Muhammad Yusuf; Shawa, Bagus Naufal Putra; Prasetyo, Andhika Rifki (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Security management refers to effective and efficient steps that must be taken to carry out security efforts and prevent losses so that disturbances that can cause losses do not occur. In the 4.0 era, people are required to utilize the latest technology to make it easier to solve problems, including data security. Cybercriminals often steal and manipulate data. Various data security methods have been developed, one of which is two factor authentication (2FA) which is widely used on social media. Gen-Z's lack of awareness about data security often leads to data leaks or account hijacking. By using 2FA, this problem can be overcome and provide more protection against cyber threats. This research aims to determine the effect of two factor authentication security on data theft on social media. This research uses qualitative methods with data collected from previous research as reference material. The results of this research show that public awareness and enlightenment regarding cybercrime is related to the use of social media.